KENAIKAN HARGA BARANG TERHADAP KONSUMSI RUMAH TANGGA SERTA DAMPAKNYA TERHADAP MOTIVASI KERJA DRIVER OJEK ONLINE - Sugiyarto Sugiyarto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study was to determine the impact of the increase in the price of basic necessities on the level of public consumption, especially in the South Tangerang City area. This study also aims to determine the impact of the increase in the price of these needed on the work motivations of online motorcycle taxi drivers in the same area. The study involved 100 respondents who were randomly selected. The research method uses descriptive quantitative methods. Data collective was carried out by interviewing and distributing questionnaires with a linkert scale, the data was processed using the path analysis method. The result showed that the increase in the price of basic necessities reduced the consumption level of people of South Tangerang by 71.4% while the increase in the price of basic needs (X) and level of public consumption (Y) simultaneously based on the result of study reduced the work motivation of online motorcycle taxi drivers (Z) as evidenced by the Sig value in the coefficients table of 0.000 while the direct effect of X to Z is 43. 7% and the indirect effect of X on Z 37.3% Thus value of the effect of X through Y on Y is 81%